Students’ Ability In Forming Passive Voice At SMAN 6 Tanjungpinang - Joko Iswanto (Jolly Journal of English Education, 2024)
This study aimed to analyze students’ ability in forming passive voice at the 11th grade of SMAN 6 Tanjungpinang. The objective of this research was to investigate the students’ ability at the 11th grade IPA I of SMAN 6 Tanjungpinang which consist of 20 students in forming passive voice. This research was an analytical study using the purposive sampling method, which was just one class as participants. The design of this research used descriptive quantitative method both quantitative was used to present the result in this research and descriptive to explain data systematically, factually, and accurately. Technique for analyzing in this research were collected the student’s test which focused on the forming of passive voice in tenses, checking the test and giving the score percentage, and categorizing the data based on the theory of the interval score by DP. Harris. After analyzing it could be seen that students’ ability in forming passive voice at the 11th grade of SMAN 6 Tanjung Pinang was considered good category, since the mean of students’ score was 73, which were specifically the classification indicated that no one student or 0 % were considered very poor, nine students or 45 % were considered excellent, six students or 30 % were considered good, three students or 15 % were considered fair, and two students or 10 % were considered poor.